2018
DOI: 10.1055/s-0038-1667187
|View full text |Cite
|
Sign up to set email alerts
|

Ask PCOS: Identifying Need to Inform Evidence-Based App Development for Polycystic Ovary Syndrome

Abstract: Women with PCOS would use a PCOS-specific app of good quality that responds to their needs and facilitates self-care; however, currently available apps are unlikely to meet their information needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Women with PCOS in this study answered that they preferred to individually set goals and receive counselling with a medical staff regarding diet and exercise therapy, weight, menstrual cycle and their gynaecological symptoms. This is consistent with a previous study that reported that they prefer a dedicated, evidence‐based PCOS application allowing interaction with PCOS experts (Boyle et al, 2018). Mobile applications, including communication, can improve self‐management and behavioural promotion (diet, physical activity and mental health), making them suitable tools for lifestyle modification (Mukerjee, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women with PCOS in this study answered that they preferred to individually set goals and receive counselling with a medical staff regarding diet and exercise therapy, weight, menstrual cycle and their gynaecological symptoms. This is consistent with a previous study that reported that they prefer a dedicated, evidence‐based PCOS application allowing interaction with PCOS experts (Boyle et al, 2018). Mobile applications, including communication, can improve self‐management and behavioural promotion (diet, physical activity and mental health), making them suitable tools for lifestyle modification (Mukerjee, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Online intervention is a cost‐effective approach that can provide patient‐centred healthcare with high accessibility and low cost (Starren et al, 2005). Various studies on mobile health applications for women with PCOS have been conducted (Alotaibi & Shaman, 2020; Boyle et al, 2018; Xie et al, 2018), and a prior study has shown that women with PCOS can reduce management costs and time by sending private messages and receiving care to their medical staff via a mobile application (Alotaibi & Shaman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This study further adds to the growing body of evidence that supports the use of digital technologies in health care. eHealth and mHealth have already been extensively used as tools for education, diagnosis, and management of pathologies such as diabetes [ 35 , 36 ], pediatric rheumatology [ 37 ], polycystic ovarian syndrome [ 38 ], and alcoholism [ 39 ]. At present, there are limited approaches available that combine evidence-based practice with health apps [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 200 health apps are released daily, and in the last 2 years, the number of available apps has doubled to reach more than 300,000 [ 10 ]. This development, which has not been specifically regulated, has led to the diffusion of some poor-quality apps [ 11 , 12 ]. Apps are downloaded from one of the operating system stores (“Play Store” for Android and “App Store” for iOS), where they are valued based on only 2 criteria (ie, the number of downloads and the user ratings) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%